Distally Based Pedicled Fibula Flap for Reconstruction of Infected Charcot’s Midtarsal Collapse—Diabetic Rocker Bottom Foot - Balakrishnan, T. M.; Pakkiri, Sathya; Nagalingam, Arounkumar; Selvaraj, R.; Jaganmohan, J. (Indian Journal of Plastic Surgery, 2021)
Introduction and Methods Diabetic rocker bottom foot with secondary infection exacts the expertise of a reconstructive surgeon to salvage the foot. The author selected 28 diabetic patients with secondarily infected Charcot’s degenerated rocker bottom feet and reconstructed their feet using distally based pedicled fibula flap. Reconstruction was done in a staged manner. Stage 1 surgery involved external fixation following debridement. In stage 2, struts were activated for distraction and arthroereisis. In stage 3, the distally based pedicled fibula was used for reconstruction and beaming of the arches.Results In this retrospective study, the author analyzed the outcome of all 28 patients using the Musculoskeletal Tumor Society Rating (MSTSR) score. The average MSTSR score was 27.536 in an average follow-up of 30.5 months. The limb salvage rate with the author’s procedure was 96.4% (p = 0.045).Conclusion Author’s protocol for the staged reconstruction and salvage of the infected diabetic rocker bottom foot, using the pedicled fibula flap, will be a new addendum in the reconstructive armamentarium of the orthoplastic approach.
Keywords: charcot’s joint; diabetic foot syndrome; distally based pedicled fibula flap; infected diabetic rocker bottom foot; orthoplastic approach